PkM Penyuluhan Tentang Pentingnya Menjaga Kesehatan Reproduksi pada Remaja di SMPN Kabupaten Bandung - Lilis Mamuroh; Sukmawati Sukmawati; Furkon Nurhakim (GUYUB: Journal of Community Engagement, 2023)
Adolescence is a period of transition from childhood to adulthood during which there are very rapid changes, both physically, psychologically, and socially. The problem that stands out is reproductive health, and if it is not addressed properly, it will hurt both long- and short-term. Overcoming this problem requires high knowledge of counseling. The aim of this community service is to increase youth knowledge about the importance of maintaining reproductive health. The methods in this service are lectures, questions and answers, and interactive discussions related to reproductive health. Counseling was attended by 35 students of SMPN Kab Bandung. This community service activity consists of 4 stages, namely: preparation, planning, implementation, and follow-up plan. To find out the effectiveness of counseling before the presentation of the material, a pre-test was carried out, and after the material was given, a post-test was carried out. While participating in the activity, the participants were quite enthusiastic, as evidenced by the many questions they asked. The results of the study showed an increase in knowledge after counseling was carried out.